Prenatal diagnosis of Silver–Russell syndrome with 8q12 deletion including the PLAG1 gene: a case report and review - Wu, Ke; Zhu, Yuying; Zhu, Qiumin (Frontiers in Genetics, 2024)
Silver-Russell syndrome (SRS) is a clinically and genetically heterogeneous disorder.A retrospective analysis of the live birth prevalence of SRS in Estonia showed 1:15,886 [1] . The most common causative genetic mechanism in the proband is loss of paternal methylation in the imprinted control region 1 (ICR1) at 11p15.5. A few studies suggested that inherited or de novo loss-of-function alterations of PLAG1 gene including the whole gene deletion and intragenic pathogenic variants could cause a rare type of SRS. To date, less than twenty unrelated PLAG1-related SRS cases have been reported and the clinical information about these cases is limited. We report the first prenatal case of SRS with 8q12 deletion (including PLAG1 gene). The fetus presented with intrauterine growth retardation, small for gestational age, relative macrocephaly at birth, protruding forehead. Unlike classical SRS cases, the fetus had micrognathia and didn't show body asymmetry. We hope that the literature review in this study provides new insight into genotype-phenotype relationships of PLAG1-related SRS.